AB0235 Use of Rituximab Compared to Anti-TNF Agents as Second and Third Line Therapy in Patients with Rheumatoid Arthritis. A Report from the Rhumadata® Clinical Database and Registry. (10th June 2014) - Choquette, D.; Raynauld, J.-P.; Bessette, L.; Fortin, I.; Haraoui, B.; Pelletier, J.-P.; Remillard, M.-A.; Sauvageau, D.; Villeneuve, E.; Coupal, L.
Abstract : Background: The order of use of biologic agents after failing a TNF inhibitor is still a question for debate. Phase III trial data in TNF-IR patients show comparable efficacy results across biologic agents and limited head-to-head studies have been published. Prospective registries offer a unique opportunity to observe the effectiveness (combined evaluation of efficacy and safety profile over time) of these agents in a clinical setting. Objectives: To evaluate if patients with rheumatoid arthritis (RA) treated with rituximab (RIT) after failing a first or a second anti-TNF agents (TNF-IR) have a different drug retention rate than patients similarly prescribed anti-TNF agents (pooled adalimumab, etanercept or infliximab) and compare the treatment strategies of using RIT as second or third biologic treatment. Methods: Data from TNF-IR RA patients prescribed adalimumab (ADA), etanercept (ETA), infliximab (INF) or rituximab (RIT) as second or third biologic agents on or after January 1st 2007 was extracted and subjects taking either ADA, ETA or INF were pooled to form the anti-TNF cohort. Baseline demographics included age, disease duration, HAQ-DI, fatigue and pain visual analog scale evaluations (VAS), TJC, SJC, DAS 28 ESR and SDAI. Five-year drug retention rates were estimated and compared using Kaplan-Meier survival estimates. Statistical analysis was performed using SAS version 9.3. RHUMADATA® is a clinical database and registry used in daily clinical practice at the IRM and CORQ. Results: The data from 226 RA patients were extracted, 153 and 73 having respectively failed a first and a second anti-TNF agent. No clinically significant differences in baseline variables were observed between treatment groups in second and third intention. The 5 year retention rates of second line RIT and anti-TNF use were 74% and 36% respectively (Log-rank p=0.002). In patients having failed two anti-TNF, subsequent use of RIT and anti-TNF agents respectively demonstrated 5 year retention rates of 48% and 24% (Log-rank p=0.004). Although numerically superior (74% vs 48%) second line use of RIT did not reach statistical difference when compared to third line usage. Conclusions: As a second line agent, in TNF-IR patients, RIT demonstrates a better 5 year retention rate than anti-TNF agents. As third line therapy, RIT is also statistically superior to anti-TNF agents. Although no statistical difference was demonstrated between second and third line RIT use, it is evident that positioning RIT as second line offers a better long term outcome. References: S.M. Du Pan, A. Scherer, C. Gabay, A. Finckh. Differential drug retention between anti-TNF agents and alternative biological agents after inadequate response to an anti-TNF agent in rheumatoid arthritis patients. Annals of the rheumatic diseases 01/2012; 71(6):997-9. Acknowledgements: The Rhumadata clinical database and registry is supported by unrestricted grant from Abbvie Canada, Amgen Canada, BMS Canada, Pfizer Canada, Roche Canada. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1890